280 BARRIERS TO OBTAINING HEALTH INSURANCE: A REALITY OR A MYTH?. (1st January 2006) - Khanum, A.; McDonald, A.
Abstract : Background: Twenty-eight percent of Houston residents are uninsured, which constitutes one of the highest uninsured rates in the entire United States. A better understanding of barriers that underserved families in Houston face obtaining health insurance is needed to help improve the health insurance attainment process. Objectives: To determine the association between sociodemographic factors and baseline knowledge of health insurance and to identify barriers experienced in obtaining health insurance. Design/Methods: This prospective cohort study is being carried out at the SuperKids Mobile Clinic with data collection to be completed by November 2005. We enrolled parents/guardians of children without health insurance. A baseline and telephone follow-up survey was used to collect data on sociodemographics, health insurance knowledge, and barriers in obtaining health insurance. Descriptive statistics, chi-squared analysis, and multivariate logistic regression were employed in analyzing the data. Preliminary Results: We found that parents/guardians who have at least a fifth-grade education (OR 7.7, 95% CI 1.33-4.49) or those with children aged 1 to 5 years (OR 8.0, 95% CI 1.03-6.61) are more likely to have heard of health insurance. African-American respondents are less likely to have heard of health insurance (OR 0.23, 95% CI 0.06-0.81). Of the 170 participants who have completed the study thus far, 52 (31%) had obtained health insurance while 118 were still without insurance. Only 43 (36%) of the 118 respondents without insurance had applied. Problems with the application process were reported by 12 (13%) of the 95 respondents who had applied for insurance. These included difficulty accumulating the application paperwork (58%) and problems obtaining the employer wage verification form (8%). Further data collection and analysis on the remaining study participants will help clarify the barriers experienced in obtaining health insurance. Conclusions: This study demonstrated specific populations that may benefit from focused counseling/education to increase their awareness of health insurance and subsequently improve health care access. In addition, barriers were also identified in the application process, which can help guide policy makers to target specific areas of improvement in this process.